Integrating computer-aided modeling and micro-simulation in multi-criteria evaluation of service infrastructure assignment approaches - Alfonso Duran; Isabel Garcia; Miguel Gutierrez (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: This paper proposes an integrated computer-supported multi-staged approach to the flexible design and multicriteria evaluation of service infrastructure assignment processes/ algorithms. Design/methodology/approach: It involves particularizing a metamodel encompassing the main generic components and relationships into process models and process instances, by incorporating structural data from the real-life system. Existing data on the target user population is fed into a micro-modeling system to generate a matching population of individual "virtual" users, each with its own set of trait values. The micro-simulation of their interaction with the assignment process of both the incumbent and the competitors generates a rich multi-dimensional output, encompassing both "revealed" and non-observable data. This enables a comprehensive multi-criteria evaluation of the foreseeable performance of the designed process/ algorithm, and therefore its iterative improvement. Findings: The research project developed a set of methodologies and associated supporting tools encompassing the modeling, micro-simulation and performance assessment of service infrastructure assignment processes. Originality/value: The proposed approach facilitates, in a multicriteria environment, the flexible modeling/design of situation-specific assignment processes/algorithms and their performance assessment when facing their case-specific user population.
Keywords: 650; Infrastructure assignment; metamodeling; microsimulation; multicriteria; simulation platforms